Targeting Insulin-Like Growth Factor-I and Insulin-Like Growth Factor–Binding Protein-3 Signaling Pathways. A Novel Therapeutic Approach for Asthma - Lee, Hyun (Am J Respir Cell Mol Biol, 2014)
Insulin-like growth factor (IGF)-I has been recognized to play critical roles in the pathogenesis of asthma, whereas IGF-binding protein (IGFBP)-3 blocks crucial physiologic manifestations of asthma. IGF-I enhances subepithelial fibrosis, airway inflammation, airway hyperresponsiveness, and airway smooth muscle hyperplasia by interacting with various inflammatory mediators and complex signaling pathways, such as intercellular adhesion molecule-1, and the hypoxia-inducible factor/vascular endothelial growth factor axis. On the other hand, IGFBP-3 decreases airway inflammation and airway hyperresponsiveness through IGFBP-3 receptor–mediated activation of caspases, which subsequently inhibits NF-κB signaling pathway. It also inhibits the IGF-I/hypoxia-inducible factor/vascular endothelial growth factor axis via IGF-I–dependent and/or IGF-I–independent mechanisms. This Translational Review summarizes the role of IGF-I and IGFBP-3 in the context of allergic airway disease, and discusses the therapeutic potential of various strategies targeting the IGF-I and IGFBP-3 signaling pathways for the management of asthma.